2019
DOI: 10.1038/s41598-019-46874-6
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage induction during localized chronic exposure to an insoluble radioactive microparticle

Abstract: Insoluble radioactive microparticles emitted by the incident at the Fukushima nuclear power plant have drawn keen interests from the viewpoint of radiation protection. Cs-bearing particles have been assumed to adhere in the long term to trachea after aspirated into respiratory system, leading to heterogeneous dose distribution within healthy tissue around the particles. However, the biological effects posed by an insoluble radioactive particle remain unclear. Here, we show cumulative DNA damage in normal human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 52 publications
2
23
0
Order By: Relevance
“…Experimental methods for detecting complex DNA damage have evolved in recent decades [24,[30][31][32][33][34][35][36]. Among several techniques [24,[30][31][32][33][34][35][36], microscopic operations coupled with an antibody against γ-H2AX [31][32][33][34] enables researchers to obtain spatial distributions of DSB induction in the cell nucleus. The adjacent degree of the DSB site can be evaluated from γ-H2AX foci volume in an assay [35,36]; however, the damage complexity at the nano-meter scale (the scale of DNA) cannot be obtained due to the limited spatial resolution from hundreds of nm to a few µm [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental methods for detecting complex DNA damage have evolved in recent decades [24,[30][31][32][33][34][35][36]. Among several techniques [24,[30][31][32][33][34][35][36], microscopic operations coupled with an antibody against γ-H2AX [31][32][33][34] enables researchers to obtain spatial distributions of DSB induction in the cell nucleus. The adjacent degree of the DSB site can be evaluated from γ-H2AX foci volume in an assay [35,36]; however, the damage complexity at the nano-meter scale (the scale of DNA) cannot be obtained due to the limited spatial resolution from hundreds of nm to a few µm [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that a Cs-BMP can adhere to lung tissue, we used two types of normal human diploid lung cell lines: WI-38 primary lung fibroblasts (RCB0702, RIKEN, Tokyo, Japan) and HBEC3-KT bronchial epithelial cells immortalized with hTERT and CDK4 (CRL-4051, ATCC, Manassas, VA, USA). WI-38 cells were maintained in Dulbecco’s modified Eagle’s medium/Nutrient Mixture F-12 (DMEM/F12) (D8437, Sigma, Kawasaki, Japan) supplemented with 10% fetal bovine serum (FBS, Nichirei Bioscience Inc., Tokyo, Japan), and the HBEC3-KT cells were maintained in bronchial epithelial cell medium (3211NZ, ScienCell, Carlsbad, CA, USA), as described in [ 8 ]. WI-38 and HBEC3-KT cells were maintained at 37 °C in a humidified atmosphere of 5% CO 2 in air.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, Cs-BMPs are assumed to adhere in the long term to normal tissues due to their insoluble nature. Considering local energy deposition around a Cs-BMP [ 8 ], normal tissues are assumed to be chronically and partially exposed at a microenvironmental scale. However, such heterogeneous dose distribution within the tissue has not been considered in evaluating the radiation risk of Cs-BMPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an in vitro study using Cs-bearing particles composed of 92.4% 137 Cs with 469.2 Bq and 7.6% 134 Cs with 38.5 Bq, Matsuya et al calculated by Monte Carlo code of PHITS (particle and heavy ion transport code system) the absorbed dose rates around the Cs-bearing particle 6 . They showed that the absorbed dose rate gradually decreased depending on the distance from the Cs-bearing particle, and there was a low absorbed dose rate of below 0.902 mGy/day at 1.65 mm from the particle.…”
Section: Introductionmentioning
confidence: 99%